PERAN PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KRISIS MORALITAS DI KALANGAN MAHASISWA PADA ERA GLOBALISASI - Andini Putri Arista; Ghinna Zahidah; Kanzi Moreano Prayoga; Abdul Fadhil (Cahaya Ilmu Bangsa Institute, 2024)
The moral crisis among students in the era of globalization is an important issue that requires serious attention. The era of globalization has positive and negative impacts on moral values, including for students. In this context, Islamic Religious Education (PAI) has a very strategic role in shaping the character and morality of students. This article aims to examine how PAI can play a role in overcoming the moral crisis of students in the era of globalization. This study uses a qualitative approach by analyzing relevant literature on PAI and student morality. The results of the study indicate that PAI can function as a strong moral fortress by introducing Islamic values that emphasize noble morals, piety, and social responsibility. Therefore, PAI needs to be organized contextually with a more relevant approach to the challenges of the times.